Conflict in One Upland and Two Coastal Communities Its in Northern Mindanao: - L. Bracamonte, NIMFA; L. Ponce, Sulpecia (ASIA PACIFIC JOURNAL OF SOCIAL INNOVATION, 2024)
This paper describes the nature and three typology of conflict in Mt. Malindang research settings Sebucal, an upland protected area in Occidental: Lapayan, Range a Natural Park, Oroquieta, Misamis rural coastal Lanao del Norte. and community in Kauswagan, Canaway, an urban coastal community in lligan City. The research makes use of utilizing triangulation approach survey, focus group discussion, key informant interviews, and the nature of secondary data analysis. Findings showed that and conflict in Sebucal involves stealing of animals area crops, petty quarrels, and boundary disputes in a protected that are interpersonal or within intragroup in nature from of the the local community. Lapayan captures the micro aspect "Mindanao problem" with the August 2008 MILF attack. It is an intergroup conflict with national and global bearing. Domestic violence that is basically interpersonallintra group in nature is alsO present. In the case of Canaway, domestic violence, conllict among neighbours, drunkenness, petty crimes, and land disputes depict the urban blight. In regard to conllict resolution, amicableinformal settlement is the modal strategy. The role of the barangay council and the lupong tagapamayapa is crucial. Lapayan’s case indicates military intervention. This study exempliies that the nature of conflict is defined by the geophysical and socioecOnomic characteristics of tho setting, as well as, the sociodemnographic and economic profile of tho local population. In a genersted typology of contlict, it may manifest a combination of any of the following simplemoderate and or complexintense. local andor nationalglobal, intergroup andlor intra group, personaldomestic andor structuralinstitutional, individuol andor societal.